Tunnel magnetoresistance sensor and method for manufacturing the same
By doping the soft magnetic layer of tunnel magnetoresistive sensors with impurities like Ti, V, Cr, Zr, Nb, Mo, Hf, or Ta, the sensors maintain soft magnetic properties and increase sensitivity and TMR ratio despite higher heat treatment temperatures.
Patent Information
- Application Number
- JP2023114308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
AI Technical Summary
In tunnel magnetoresistive sensors, increasing the heat treatment temperature during manufacturing to promote solid phase epitaxy at the CoFeB/MgO interface leads to a decrease in sensitivity due to the loss of soft magnetic characteristics and increased anisotropic magnetic field.
Incorporating impurities such as Ti, V, Cr, Zr, Nb, Mo, Hf, or Ta into the soft magnetic layer of the free layer, allowing for higher heat treatment temperatures without losing soft magnetic properties, thereby promoting solid phase epitaxy and increasing the TMR ratio and sensitivity.
The method enhances the heat resistance and sensitivity of the tunnel magnetoresistive sensor by maintaining soft magnetic properties and increasing the TMR ratio through higher heat treatment temperatures.
Smart Images

Figure 2025011895000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a tunneling magnetoresistive sensor and a method for manufacturing the same. [Background technology]
[0002] As a magnetic sensor using a magnetoresistance effect element, there is a tunnel magnetoresistance sensor (TMR sensor) that uses the TMR effect of a TMR element, and one of them is a tunnel magnetoresistance sensor that combines a magnetic tunnel junction (MTJ) element having a three-layer structure of CoFeB / MgO / CoFeB with a CoFeSiB layer that exhibits excellent soft magnetic properties, which has been developed by the present inventors (see, for example, Non-Patent Documents 1 and 2, and Patent Documents 1 and 2). This tunnel magnetoresistance sensor has high sensitivity enough to detect the human biomagnetic field because it simultaneously obtains a large TMR ratio of the MTJ element and a small anisotropic magnetic field of the CoFeSiB layer (see, for example, Non-Patent Documents 3 to 6).
[0003] It has also been reported that when Ta and Hf are added as impurity elements to an amorphous CoFeSiB thin film, which is a soft magnetic material used in the yoke of a GIGS sensor, the crystallization temperature is increased and the soft magnetic properties are maintained even after heat treatment (see, for example, Non-Patent Document 7). It has also been reported that when Ta and Hf are added to an amorphous CoFeB thin film, the crystallization temperature is increased (see, for example, Non-Patent Documents 8 to 10). [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] “ Fabrication of Magnetic Tunnel Junctions with Amorphous CoFeSiB Ferromagnetic Electrode for Magnetic Field Sensor Devices ,” Appl. Phys. Express , 2013 , 6 , 103004
Outdoor Tool2
Outdoor Tools3
Outdoor Tools 4
Direct Environment 5
Outdoor Configuration6
Direct Environment 7
Non-Patent Document 8
Non-Patent Document 9
Non-Patent Document 10
Patent Document
[0005] [Patent Document 1] JP 2020-136551 A [Patent Document 2] JP 2020-136552 A Summary of the Invention [Problem to be solved by the invention]
[0006] In the tunnel magnetoresistance sensor, if the heat treatment temperature during manufacturing is increased, for example, solid-phase epitaxy at the interface of CoFeB / MgO of the MTJ element is promoted, so that it is expected that the TMR ratio will increase and the sensitivity of the sensor will also increase. However, in the tunnel magnetoresistance sensors described in Non-Patent Documents 1 to 6 and Patent Documents 1 and 2, if the CoFeSiB layer is subjected to a high-temperature heat treatment exceeding its crystallization temperature (up to 300°C) during manufacturing, the soft magnetic properties will be lost, the anisotropic magnetic field will increase, and the sensitivity of the sensor will decrease, so there is a problem that there is a limit to how high the heat treatment temperature can be increased.
[0007] The present invention has been made in light of these problems, and aims to provide a tunnel magnetoresistance sensor and a manufacturing method thereof that can improve heat resistance and further increase the TMR ratio and sensitivity. [Means for solving the problem]
[0008] In order to achieve the above-mentioned object, the tunnel magnetoresistive sensor of the present invention has a fixed layer whose magnetization direction is fixed, a free layer whose magnetization direction is changeable, and a barrier layer containing a non-magnetic material and arranged between the fixed layer and the free layer, and the free layer is characterized in that the free layer has a ferromagnetic layer arranged on the barrier layer side, and a soft magnetic layer arranged on the opposite side of the ferromagnetic layer from the barrier layer and made of a soft magnetic material to which impurities have been added.
[0009] In the tunnel magnetoresistance sensor according to the present invention, the crystallization temperature of the soft magnetic layer of the free layer can be increased by adding impurities to the soft magnetic layer, and the heat resistance can be improved. Therefore, the heat treatment temperature during manufacturing can be increased, and the solid phase epitaxy of the interface between the fixed layer and the barrier layer and the interface between the barrier layer and the free layer can be promoted, and the TMR ratio can be further increased. In addition, the anisotropic magnetic field of the soft magnetic layer of the free layer can be reduced to further improve the soft magnetic properties, and therefore the sensitivity can be further increased.
[0010] In the tunneling magnetoresistance sensor according to the present invention, the ferromagnetic layer is preferably made of CoFeB, and the soft magnetic layer is preferably made of a soft magnetic material in which at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W is added as the impurity to a base material CoFeSiB. In this case, the TMR ratio and sensitivity can be particularly improved. In addition, in this case, the soft magnetic layer may contain impurities at 10 at% or less, 15 at% or less, or even 20 at% or less of the base material, since the TMR ratio and sensitivity are higher as the soft magnetic layer contains more impurities.
[0011] In the tunneling magnetoresistive sensor according to the present invention, the pinned layer is preferably made of CoFeB, and the barrier layer is preferably made of MgO. Also, in the tunneling magnetoresistive sensor according to the present invention, the soft magnetic layer is preferably formed of an amorphous structure. In these cases, the TMR ratio and sensitivity can be particularly improved.
[0012] The manufacturing method of the tunneling magnetoresistive sensor according to the present invention is a manufacturing method of the tunneling magnetoresistive sensor for manufacturing the tunneling magnetoresistive sensor according to the present invention, and is characterized in that after forming the fixed layer, the barrier layer and the free layer, a heat treatment is performed at 325°C to 425°C.
[0013] In the method for manufacturing a tunnel magnetoresistance sensor according to the present invention, since the soft magnetic layer of the free layer is doped with impurities, heat treatment can be performed at 325°C to 425°C, which is higher than the crystallization temperature of a soft magnetic layer without doping with impurities. This can promote solid-phase epitaxy at the interface between the fixed layer and the barrier layer and the interface between the barrier layer and the free layer, and can further increase the TMR ratio of the tunnel magnetoresistance sensor. In addition, the anisotropic magnetic field of the soft magnetic layer of the free layer can be reduced to further improve the soft magnetic properties, and therefore the sensitivity of the tunnel magnetoresistance sensor can be further increased. Effect of the Invention
[0014] According to the present invention, it is possible to provide a tunnel magnetoresistance sensor capable of improving heat resistance and further increasing the TMR ratio and sensitivity, and a method for manufacturing the same. [Brief description of the drawings]
[0015] [Figure 1] 1 is a longitudinal sectional view of a tunnel magnetoresistive sensor according to an embodiment of the present invention; [Diagram 2] 5A shows a magnetization curve for each heat treatment temperature when x=0.0 at.%, (b) a magnetization curve for each heat treatment temperature when x=4.1 at.%, (c) a magnetization curve for each heat treatment temperature when x=7.9 at.%, (d) a graph showing the relationship between saturation magnetization Ms and x, (e) a graph showing the relationship between anisotropy magnetic field Hk and x, and (f) a graph showing the relationship between uniaxial magnetic anisotropy constant Ku and saturation magnetization Ms for the soft magnetic layer (CoFeSiB)1-xTax of the free layer of a tunnel magnetoresistance sensor according to an embodiment of the present invention. [Diagram 3] FIG. 1 shows (a) XRD spectra before heat treatment (As depo.) and after heat treatment at 500°C for (CoFeSiB)1-xTax, a soft magnetic layer of a free layer of a tunnel magnetoresistance sensor according to an embodiment of the present invention, when x=0.0 at.%, (b) XRD spectra before heat treatment (As depo.) and after heat treatment at 500°C for (CoFeSiB)1-xTax, when x=7.9 at.%, and (c) an AFM (atomic force microscope) image before heat treatment for (CoFeSiB)1-xTax, when x=7.9 at.%. [Figure 4]1A is a graph showing, for a tunnel magnetoresistance sensor according to an embodiment of the present invention, (a) a magnetoresistance curve for each heat treatment temperature when the x of the soft magnetic layer (CoFeSiB)1-xTax of the free layer is x=0.0 at.%, (b) a magnetoresistance curve for each heat treatment temperature when x=2.8 at.%, (c) a magnetoresistance curve for when the heat treatment temperature is 325°C for x=0.0 at.% and when the heat treatment temperature is 400°C for x=2.8, 4.1, and 5.9 at.%, and (d) a graph showing the sensitivity S calculated from (c) and its maximum value Smax (inset). [Diagram 5] FIG. 1 shows a scanning transmission electron microscope (STEM) image of a tunnel magnetoresistance sensor according to an embodiment of the present invention, where (a) is a scanning transmission electron microscope (STEM) image at a heat treatment temperature of 400°C for x=0.0 at.%, (b) is a STEM image at a heat treatment temperature of 400°C for x=2.8 at.%, (c) is an enlarged STEM image of a portion of (a) and an NBD pattern (inset) at the position of the asterisk in (a), and (d) is an enlarged STEM image of a portion of (b) and an NBD pattern (inset) at the position of the asterisk in (b). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. 1 to 5 show a tunneling magnetoresistive sensor (TMR sensor) according to an embodiment of the present invention. As shown in FIG. 1, the tunneling magnetoresistive sensor 10 includes a substrate 11 , a bottom electrode layer 12 , a free layer 13 , a barrier layer 14 , a pinned layer 15 and a top electrode layer 16 .
[0017] The tunneling magnetoresistance sensor 10 is formed by depositing a lower electrode layer 12, a free layer 13, a barrier layer 14, a fixed layer 15, and an upper electrode layer 16 in that order on a substrate 11 using a physical vapor deposition method such as sputtering or molecular beam epitaxial growth (MBE).
[0018] The substrate 11 is made of a Si wafer or a Si wafer with a thermal oxide film. The lower electrode layer 12 is provided on the surface of the substrate 11. The lower electrode layer 12 may be made of any conductive material. The lower electrode layer 12 is made of, for example, Cu, Ta, Ru, or a laminated structure thereof. In the specific example shown in FIG. 1, the lower electrode layer 12 is made of Ta / Ru / Ta.
[0019] The free layer 13 is provided on the surface of the lower electrode layer 12 opposite to the substrate 11. The free layer 13 has a structure in which a soft magnetic layer 21, a first non-magnetic layer 22, and a first ferromagnetic layer 23 are laminated in this order on the lower electrode layer 12. The soft magnetic layer 21 is capable of changing its magnetization direction under the influence of an external magnetic flux. The soft magnetic layer 21 is made of a soft magnetic material with an amorphous structure to which an impurity is added, and preferably has a layer thickness of about 30 nm to 200 nm. In a specific example shown in FIG. 1, the soft magnetic layer 21 is made of a soft magnetic material in which Ta is added as an impurity to a base material CoFeSiB, and has a layer thickness of 100 nm. The impurity is not limited to Ta, and may be, for example, Ti, V, Cr, Zr, Nb, Mo, Hf, or W. The impurity is preferably contained at 20 at % or less with respect to the base material.
[0020] The first nonmagnetic layer 22 is provided to magnetically couple the soft magnetic layer 21 and the first ferromagnetic layer 23, and to separate the soft magnetic layer 21 from the crystal structure of the first ferromagnetic layer 23. The first nonmagnetic layer 22 is preferably made of a nonmagnetic material such as Ta, Mo, W, or Ru, or an alloy containing these, and has a thickness of about 0.2 to 1 nm. In a specific example shown in FIG. 1, the first nonmagnetic layer 22 is made of Ta and has a thickness of 0.2 nm.
[0021] The magnetization direction of the first ferromagnetic layer 23 can be changed by the influence of an external magnetic flux. The first ferromagnetic layer 23 is preferably made of a ferromagnetic material such as CoFeB and has a thickness of about 1 to 5 nm. In a specific example shown in FIG. 1, the first ferromagnetic layer 23 is made of CoFeB and has a thickness of 3 nm.
[0022] The barrier layer 14 is provided on the surface of the free layer 13 opposite the lower electrode layer 12, i.e., on the surface of the first ferromagnetic layer 23 of the free layer 13 opposite the first nonmagnetic layer 22. The barrier layer 14 is made of an insulating material such as MgO, Mg-Al-O, AlOx, etc., and preferably has a layer thickness of about 1 nm to 5 nm. In the specific example shown in FIG. 1, the barrier layer 14 is made of MgO.
[0023] The fixed layer 15 is provided on the surface of the barrier layer 14 opposite to the free layer 13, so as to sandwich the barrier layer 14 between the free layer 13 and the fixed layer 15. The fixed layer 15 has a structure in which a second ferromagnetic layer 24, a second non-magnetic layer 25, a third ferromagnetic layer 26, and a fixation promotion layer 27 are laminated in this order on the barrier layer 14. The magnetization direction of the second ferromagnetic layer 24 is fixed. The second ferromagnetic layer 24 is preferably made of a ferromagnetic material such as CoFeB, and has a layer thickness of about 1 nm to 5 nm. In a specific example shown in FIG. 1, the second ferromagnetic layer 24 is made of CoFeB and has a layer thickness of 3 nm.
[0024] The second nonmagnetic layer 25 is provided to magnetically couple the second ferromagnetic layer 24 and the third ferromagnetic layer 26 and to separate the second ferromagnetic layer 24 from the crystal structure of the third ferromagnetic layer 26. The second nonmagnetic layer 25 is preferably made of a nonmagnetic material such as Ir or Ru and has a thickness of about 0.2 to 1 nm. The second nonmagnetic layer 25 may have a structure in which a nonmagnetic layer made of Ta, Mo, W, or the like is provided on the second ferromagnetic layer 24, a ferromagnetic layer such as CoFe is disposed thereon, and a nonmagnetic layer such as Ir or Ru is further provided thereon. In a specific example shown in FIG. 1, the second nonmagnetic layer 25 is made of Ru and has a thickness of 0.9 nm.
[0025] The magnetization direction of the third ferromagnetic layer 26 is fixed. The third ferromagnetic layer 26 is preferably made of a ferromagnetic material such as CoFe and has a thickness of about 1 nm to 5 nm. In the specific example shown in FIG. 1, the third ferromagnetic layer 26 is made of CoFe and has a thickness of 2 nm.
[0026] The fixation promoting layer 27 is provided to promote fixation of the third ferromagnetic layer 26. The fixation promoting layer 27 is made of an antiferromagnetic material such as IrMn or PtMn, and has a layer thickness of about 5 nm to 20 nm. In the specific example shown in FIG. 1, the fixation promoting layer 27 is made of IrMn and has a layer thickness of 10 nm.
[0027] The upper electrode layer 16 is provided on the surface of the fixation promotion layer 27 opposite to the third ferromagnetic layer 26. The upper electrode layer 16 may be made of any conductive material. The upper electrode layer 16 is made of, for example, Ta, Ru, Pt, or a laminated structure thereof. In the specific example shown in FIG. 1, the upper electrode layer 16 is made of Ta / Ru.
[0028] In order to obtain a desired crystal structure, the tunneling magnetoresistive sensor 10 is heat-treated after deposition of each layer by the method for manufacturing the tunneling magnetoresistive sensor according to the embodiment of the present invention. The heat treatment temperature is 325° C. to 425° C., which is higher than the crystallization temperature of the soft magnetic layer without doping.
[0029] Next, the operation will be described. In the tunnel magnetoresistance sensor 10, by adding impurities to the soft magnetic layer 21 of the free layer 13, the crystallization temperature of the soft magnetic layer 21 can be increased, and the heat resistance can be improved. This allows the heat treatment temperature during manufacturing to be increased, promoting solid phase epitaxy at the interface between the fixed layer 15 and the barrier layer 14 and at the interface between the barrier layer 14 and the free layer 13, and thus increasing the TMR ratio. In addition, the anisotropic magnetic field of the soft magnetic layer 21 of the free layer 13 can be reduced to further improve the soft magnetic properties, thereby further increasing the sensitivity. EXAMPLES
[0030] The soft magnetic layer 21 of the free layer 13 (CoFeSiB) 1-x Ta x(hereinafter, also referred to as "CoFeSiB(Ta)") was manufactured and its magnetic properties, etc. were examined. As a test sample, a thermally oxidized Si(100) substrate was used as the substrate 11, and the layers were deposited thereon in the order of Ta(5) / CoFeSiB(Ta)(30) / Ta(2) by sputtering. The numbers in parentheses indicate the film thickness (unit: nm). In addition, when depositing the soft magnetic layer 21 CoFeSiB(Ta), CoFeSiB(Ta) was used as the target. 70.5 Fe 4.5 S 15 B 10 Five types of samples were manufactured with different Ta contents x by co-sputtering using a ferromagnetic material. The test samples manufactured had x = 0.0, 2.8, 4.1, 5.9, and 7.9 at.%. After each layer was formed, a heat treatment was performed in a magnetic field at 300°C to 500°C to induce uniaxial magnetic anisotropy.
[0031] For each test sample, a vibrating sample magnetometer (VSM) was used to determine the magnetization curve (MH curve) in an in-plane magnetic field parallel to the hard axis of magnetization. The magnetization curves for the test samples with x=0.0, 4.1, and 7.9 at.% when the heat treatment temperatures were 300°C and 400°C are shown in Figures 2(a) to (c), respectively. As shown in Figure 2(a), for the test sample with x=0.0 at.%, the coercivity H c is 0.7 Oe, and the anisotropy field H k However, when the heat treatment temperature was 400° C., the coercive force became 690 Oe, and it was confirmed that the soft magnetic properties were lost.
[0032] As shown in Fig. 2(b), in the test sample with x = 4.1 at.%, when the heat treatment temperature was 300°C, the anisotropy magnetic field H k At a heat treatment temperature of 400°C, the anisotropy magnetic field H k As shown in Fig. 2(c), the anisotropic magnetic field H kIt was confirmed that the magnetic anisotropy was almost completely eliminated, with the magnetic field being extremely small below 1 Oe.
[0033] From the magnetization curve of each test sample, the saturation magnetization M s , anisotropy magnetic field H k , and the uniaxial magnetic anisotropy constant K u (=M s ×H k As shown in FIG. 2(d), the saturation magnetization M s It was confirmed that, regardless of the heat treatment temperature, the anisotropy magnetic field H k It was also confirmed that, regardless of the heat treatment temperature, the thermal resistance decreases as the Ta content x increases. In addition, the rate of decrease is faster when the heat treatment temperature is 400°C than when it is 300°C, so it was confirmed that the heat resistance improves rapidly with an increase in Ta. In addition, as shown in Figure 2(f), the uniaxial magnetic anisotropy constant K u is the saturation magnetization M s It was confirmed that as the value of
[0034] Next, the test samples with x=0.0 at.% and 7.9 at.% were measured by X-ray diffraction before heat treatment (As depo.) and after heat treatment at 500°C. The respective XRD spectra are shown in Figs. 3(a) and (b). As shown in Figs. 3(a) and (b), no clear difference was observed between the sample not containing Ta (x=0.0 at.%) and the sample containing Ta (x=7.9 at.%). In addition, regardless of the value of the Ta content rate x and the heat treatment temperature, a broad peak was observed between 2θ=44° and 49°, so it is considered that the CoFeSiB(Ta) of the soft magnetic layer 21 has an amorphous or nanocrystalline structure.
[0035] An AFM (atomic force microscope) image of the test sample with x=7.9 at.% before the heat treatment is shown in FIG. 3(c). As shown in FIG. 3(c), the surface of the soft magnetic layer 21 CoFeSiB(Ta) is very smooth, with an arithmetic mean surface roughness (R a ) and root mean square surface roughness (R q ) were confirmed to be 0.16 nm and 0.20 nm, respectively. These values are almost the same as the surface roughness of the test sample that does not contain Ta (x=0.0 at.%). EXAMPLES
[0036] A tunnel magnetoresistance (TMR) sensor shown in Figure 1 was manufactured and its magnetic properties were examined. A thermally oxidized Si(100) substrate was used as the substrate 11 for the test sample of the TMR sensor, and each layer of the following structure was formed thereon by sputtering. The numbers in parentheses indicate the film thickness (unit: nm). Ta (5) / Ru (40) / Ta (5) / CoFeSiB(Ta) (100) / Ta (0.2) / Co 40 Fe 40 B 20 (3) / MgO / Co 40 Fe 40 B 20 (3) / Ta 80 B 20 (0.1) / Co 75 Fe 25 (0.8) / Ru (0.8) / Co 75 Fe 25 (3) / Ir 22 Mn 78 (10) / Ta (2) / Ru (7)
[0037] In addition, as in Example 1, when forming the soft magnetic layer 21 CoFeSiB(Ta), a target of Co 70.5 Fe 4.5 S 15 B 10Four types of samples were manufactured with different Ta contents x by co-sputtering using a SiO2 film. The test samples manufactured had x = 0.0, 2.8, 4.1, and 5.9 at.%. After each layer was formed, it was heat-treated at 325°C to 425°C.
[0038] For each test sample, the magnetoresistance curve was measured in an in-plane magnetic field parallel to the hard axis of magnetization. Figure 4(a) shows the magnetoresistance curves of the test sample with x=0.0 at.% when the heat treatment temperatures were 325°C, 350°C, and 375°C, and Figure 4(b) shows the magnetoresistance curves of the test sample with x=2.8 at.% when the heat treatment temperatures were 325°C, 350°C, 375°C, 400°C, and 425°C. As shown in Figure 4(a), it was confirmed that the TMR ratio changed linearly with the magnetic field in the test sample with x=0.0 at.% when the heat treatment temperature was 325°C. However, when the heat treatment temperature was 350°C or higher, the coercive force H c It was confirmed that the soft magnetic properties disappeared.
[0039] As shown in Fig. 4(b), in the test sample with x=2.8 at.%, it was confirmed that the TMR ratio changed linearly with the magnetic field at all heat treatment temperatures. This confirmed that the soft magnetic properties were maintained at least up to a heat treatment temperature of 425°C, and that the addition of Ta improved the heat resistance. It was also confirmed that the TMR ratio increased from 183% to 228% as the heat treatment temperature increased. This is believed to be due to the promotion of solid-phase epitaxy at the CoFeB / MgO interface.
[0040] Figure 4(c) shows the magnetoresistance curve of the test sample with x=0.0 at.% when the heat treatment temperature is 325°C (the same as the curve in Figure 4(a)), and the magnetoresistance curves of the test samples with x=2.8, 4.1, and 5.9 at.% when the heat treatment temperature is 400°C. As shown in Figure 4(c), it was confirmed that the samples containing Ta had a higher TMR ratio than the samples not containing Ta (x=0.0 at.%). This is believed to be because the heat treatment temperature could be increased. It was also confirmed that the slope of the magnetoresistance curve became steeper as the Ta content x increased. This is because the anisotropic magnetic field H k This is thought to be because the θ becomes smaller (see Fig. 2(e)).
[0041] The sensitivity S of each TMR sensor was calculated from the slope of the magnetoresistance curve of each test sample in Fig. 4(c), and is shown in Fig. 4(d). As shown in Fig. 4(d), the maximum value S of the sensitivity S was reached when the free layer 13 of the TMR sensor was in the middle of the magnetization reversal (near the middle of the magnetization reversal). max It was confirmed that the maximum sensitivity S was obtained. max is plotted against the Ta content x, as shown in the inset of Fig. 4(d). As shown in Fig. 4(d), in the case of a Ta-free sample (x=0.0 at.%), the maximum value of the sensitivity S is S max As the Ta content x increases, the maximum value of the sensitivity S becomes max In the TMR sensor with x=5.9 at.%, the maximum sensitivity S is S max It was confirmed that the annealing efficiency was 50 % / Oe.
[0042] Cross-sections of the test samples with x=0.0 and 2.8 at.% and heat treatment temperature of 400°C were observed by scanning transmission electron microscope (STEM). The STEM images are shown in Fig. 5(a) and (b). As shown in Fig. 5(a), it was confirmed that the CoFeSiB of the soft magnetic layer 21 containing no Ta (x=0.0 at.%) contains crystal grains with a diameter of several tens of nm in an amorphous structure. In contrast, as shown in Fig. 5(b), it was confirmed that the CoFeSiB(Ta) of the soft magnetic layer 21 containing Ta (x=2.8 at.%) has a uniform amorphous structure.
[0043] Enlarged STEM images of Fig. 5(a) and (b) are shown in Fig. 5(c) and (d), respectively. In addition, the NBD patterns at the positions of the asterisks in Fig. 5(a) and (b) by nanobeam diffraction (NBD) are shown in the insets of Fig. 5(c) and (d), respectively. As shown in Fig. 5(c), it was confirmed that the CoFeSiB of the soft magnetic layer 21 that does not contain Ta (x=0.0 at.%) has a crystal grain boundary (dotted line in the figure), and that one side of the crystal grain boundary (left side of the dotted line in the figure) shows a lattice pattern, and the other side (right side of the dotted line in the figure) shows an isotropic maze pattern. From the NBD pattern, it was confirmed that the side showing the lattice pattern is a crystal with a face-centered cubic (fcc) structure with a lattice constant of 0.336 nm.
[0044] As shown in FIG. 5(d), it was confirmed that the CoFeSiB(Ta) of the soft magnetic layer 21 containing Ta (x=2.8 at.%) exhibited an isotropic maze pattern. In addition, since the NBD pattern was circular, it was confirmed that the soft magnetic layer 21 had a structure in which a large number of face-centered cubic nanocrystals were oriented in random directions. It was also confirmed that the lattice constant of the nanocrystals was 0.336 nm. From these results, it can be said that the crystallization temperature can be increased to at least 400° C. by adding Ta to the soft magnetic layer 21. [Explanation of symbols]
[0045] 10 Tunneling magnetoresistance sensor 11 Substrate 12 Lower electrode layer 13 Free layer 21 Soft magnetic layer 22 First nonmagnetic layer 23 First ferromagnetic layer 14 Barrier Layer 15 Fixed layer 24 Second ferromagnetic layer 25 Second nonmagnetic layer 26 Third ferromagnetic layer 27 Immobilization promotion layer 16 Upper electrode layer
Claims
1. a fixed layer whose magnetization direction is fixed; A free layer having a changeable magnetization direction; a barrier layer including a non-magnetic material and disposed between the pinned layer and the free layer; The free layer has a ferromagnetic layer disposed on the barrier layer side, and a soft magnetic layer disposed on the opposite side of the ferromagnetic layer from the barrier layer and made of a soft magnetic material to which an impurity is added. A tunnel magnetoresistive sensor.
2. the ferromagnetic layer is made of CoFeB; The soft magnetic layer is made of a soft magnetic material in which at least one of Ti, V, Cr, Zr, Nb, Mo, Hf, Ta, and W is added as the impurity to a base material of CoFeSiB.
2. The tunneling magnetoresistive sensor according to claim 1.
3. 3. The tunneling magnetoresistive sensor according to claim 2, wherein the soft magnetic layer contains the impurity in an amount of 20 at % or less with respect to the base material.
4. the pinned layer is made of CoFeB; The barrier layer is made of MgO.
3. The tunneling magnetoresistive sensor according to claim 2.
5. 2. The tunneling magnetoresistive sensor according to claim 1, wherein the soft magnetic layer has an amorphous structure.
6. A method for manufacturing a tunneling magnetoresistive sensor according to any one of claims 1 to 5, comprising the steps of: After the pinned layer, the barrier layer, and the free layer are deposited, a heat treatment is performed at 325° C. to 425° C. A method for manufacturing a tunnel magnetoresistive sensor.
Citation Information
Patent Citations
Tunnel magnetoresistive element and tunnel magnetic resistance sensor
JP2020136551A
Tunnel magnetic resistance sensor
JP2020136552A